THE EFFECT OF BASIC LIFE SUPPORT (BLS) EDUCATION ON THE SKILL LEVEL OF NURSING STUDENT ASSOCIATION MEMBERS: A QUASI-EXPERIMENTAL STUDY - Ferry Fadli Fratama; Ria Roswita; Nurhayati Nurhayati; Bisepta Prayogi; Ria Anggara Hamba (Poltekkes Kemenkes Banjarmasin, 2026)
Basic Life Support (BLS) is an essential initial intervention in emergency care to maintain a patient’s vital functions. Nursing students, as future healthcare professionals, need to have strong BLS skills through structured education. This study aimed to determine the effect of Basic Life Support (BLS) education on the skill levels of students in the Nursing Student Association. This research used a quasi-experimental design with a one-group pretest-posttest approach. The number of respondents was 30 students selected using a purposive sampling technique. Data were collected using an observation checklist of BLS skills before and after the educational intervention. Data analysis was performed using the Wilcoxon Signed Rank Test to determine differences in skill levels before and after the intervention. The results showed an improvement in students' skills after receiving BLS education. Based on the Wilcoxon test results, the p-value obtained was 0.000 (p < 0.05), indicating a significant effect of Basic Life Support (BLS) education on students' skill levels. In conclusion, Basic Life Support (BLS) education has a significant impact on improving nursing students’ skills. It is recommended that BLS education be conducted continuously and in a structured manner to enhance students’ competence in handling emergency situations.